Effects Of Perceived Usefulness And Perceived Ease Of Use For Driving Purchase Intention - Nevynda Diella Pratista; Endy Gunanto Marsasi (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
The purpose of this research is to look at how several factors, including quantity, quality of arguments, source credibility, perceived usability and utility, attitude toward buying, attitude toward brands, and intention to buy, affect Generation Z. The primary concept used in this research is the Technology Acceptance Model (TAM) idea. The data collection technique uses non-probability sampling with a purposive sampling method. There were 243 people included in the sample for this investigation. The statistical packages IBM SPSS 27 and AMOS Graphic 24 were used for this quantitative study. Perceived usefulness and ease of use were not shown to be positively and significantly related in this study's hypothesis results. Attitude toward the purchase is positively and significantly impacted by perceived utility. Additionally, there is a favorable and statistically significant correlation between buy attitude and brand attitude, according to the data analysis.